Automotive Security Penetration Testing - Pedro Filipe Agostinho Soares Pinto (2019)
These days, vehicles are composed mainly by electronic components and systems, designed to make our lives easier and more comfortable. However, with more significant amounts of electronics, the change of a vehicle being compromised also increases. This can be done by different means and approaches, but it is the manufacturers' responsibility to assure a secure product. One of the goals of AUTOSAR, being the same a worldwide development partnership of automotive interested parties, is to grant well-protected outputs. For this, some measures have been taken into account, like the development of security use cases. These, if successfully implemented and tested, provide additional defence against unintended users and attacks. This Master Thesis aims to verify the particular use case of Secure Variant Coding, making sure that a user without the right credentials cannot access undesired aspects of the system. This use case will be implemented in an Electronic Control Unit (ECU) being developed by BOSCH, where all the tests will be made, making use of the proper tools and approaches for this matter.